Experimental model of the formation of readiness of commanders of military subdivisions for pedagogical facilitation - Predytkevych, O. S. (Problems of Engineer-Pedagogical Education, 2018)
The problem of the formation of readiness of commanders of military subdivisions for pedagogical facilitation is outlined. To achieve the defined aim the method of pedagogical design was used. An experimental model must have the sufficient degree of its coordination with the environment, be maximally close to reality, complete, accurate and true to achieve some definite goals. Taking into account the essence of the professional activity of commanders of military subdivisions, the model of the formation of military service members’ readiness for pedagogical facilitation is worked out, which consists of interrelated and interacting blocks such as motivational and goal-oriented, organizational, procedural-substantive, criterion-estimating, oriented at the achievement of the optimal level of pedagogical facilitation of commanders of military subdivisions. The substantial study of separate structural elements of the author’s model allow generalizing the results that base on the technique of the formation of readiness of commanders of military subdivisions for pedagogical facilitation which is realized with the help of previously acquired psychological and pedagogical knowledge and competences. The result of the realization of the model is the training of professional commanders of military subdivisions in the system of postgraduate education who are able to organize military service of the Armed forces of Ukraine.